2013
DOI: 10.4028/www.scientific.net/amr.845.642
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Lean Manufacturing Tools Implementation in Malaysian Food and Beverages Industry Using Rasch Model

Abstract: This paper offers a preliminary study on Lean Tools (LT) implementation in Malaysian Food and Beverages Industry. A survey was carried out to determine the most common LT that are currently being implemented in this industry. Out of 1309, a total of 300 organizations have been randomly selected as respondents. The results were analyzed using Rasch Model, and the findings show that the organizations apply only six out of eighteen LT. From the variable map, Kaizen is the most preferable LT, while Single Minute E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
(10 reference statements)
0
14
0
Order By: Relevance
“…As displayed in Figure 4, the Cronbach's alpha (α) and person reliability values were 0.96 and 0.95, respectively. With the value of more than 0.7 (Cronbach's alpha (α) and person reliability), it was proven that using another set of items to measure similar study with a similar set of person placement was equitable [37]. This indicated that the instrument's internal consistency in measuring the respondents' conceptual comprehension of the topic was excellent [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As displayed in Figure 4, the Cronbach's alpha (α) and person reliability values were 0.96 and 0.95, respectively. With the value of more than 0.7 (Cronbach's alpha (α) and person reliability), it was proven that using another set of items to measure similar study with a similar set of person placement was equitable [37]. This indicated that the instrument's internal consistency in measuring the respondents' conceptual comprehension of the topic was excellent [35].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to obtain a good data analysis of survey questionnaire, a statistical software for Rasch model analysis named Winstep software V3.72.3 was used. Literature studies showed that the Rasch model has been used in other research fields such as education [32]- [36], food and beverages [23], [37], medical [24], and sport [38] and it was proven capable to measure any subjective assessment. At the same time, Rasch is also capable to convert all ordinal data into ratio data.…”
Section: Discussionmentioning
confidence: 99%
“…Goshime et al (2019) reported that most industries in the developing countries are still in an infant stage in adopting the LM philosophy, while Yadav et al (2020b) asserted that many organizations have not yet adopted the LM philosophy in the developing world. The developing countries lack the expertise that helps in the implementation of LM (Hokoma et al , 2010; Ghosh, 2013; Khusaini et al , 2014), and there is also more knowledge of LM in the developed countries compared to the developing countries (Hokoma et al , 2010; Panwar et al , 2016). In addition to that, authors such as Khaba and Bhar (2018), Shamah (2013) and Wong and Wong (2011) averred that some employees fear losing their jobs due to retrenchment when non-value-added activities become visible.…”
Section: Introductionmentioning
confidence: 99%
“…The first type of these studies involves adopting various traditional methods, and some of these methods include certain limitations inherent in the method itself used in these studies. For example, one of these models requires someone with powerful information of mathematical methods and good experiences that are required to evaluate the criteria of the methods (Khusaini et al , 2014; Pelton, 2002). Also, another method requires that the user constantly update in order to remain up-to-date with the advancements and availability of technologies and administrative procedures (Wan and Chen, 2009).…”
Section: Introductionmentioning
confidence: 99%